The absorption of EU funds and the socio-economic development in the subregional dimension in Poland - Spychała, Marcin (Absorpcja funduszy Unii Europejskiej a rozwój społeczno-ekonomiczny w ujęciu subregionalnym w Polsce, 2020)
The purpose of the article is to specify the interdependencies between the absorption of EU funds and the changes in socio-economic development. The research was conducted on subregional level in three stages. At the first stage, the level of development of 380 districts in Poland was specified. At the second stage, the differentiation in EU fund absorption in those districts was shown. At the third stage, the interdependencies between the size of the absorption and the changes in the level of development in the arrangement of factors of the said development based on the analysis of regression was specified
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 78-91
Keywords: EU funds; socio-economic development; synthetic gauge; fundusze unijne; rozwój społeczno-ekonomiczny; miernik syntetyczny